The role of inflammation and infection in coronary artery disease - Becker, A E; de Boer, O J; van Der Wal, A C (Annual review of medicine, 2001)
New insights into atherosclerosis, the most common disease affecting coronary arteries, may change therapeutic strategies from largely symptomatic to causal. Atherosclerotic plaques contain a lipid-related, immune-mediated inflammation, with release of secretory products capable of changing plaque morphology. Plaques prone to complications contain large numbers of inflammatory cells; stable plaques contain little inflammation. Similarly, atherectomy specimens from patients with coronary syndromes revealed more inflammatory cells in unstable than in stable patients. These observations, and the fact that acute coronary syndromes are associated with increased blood levels of inflammatory markers, have renewed interest in the possible relationship between infection and atherogenesis. Of all potential candidate antigens, Chlamydia pneumoniae presently is considered the most likely because a substantial number of patients with unstable syndromes contain C. pneumoniae-reactive T cells, both in blood and within the atherosclerotic plaque, suggesting enhancement of intraplaque inflammation.